2018
DOI: 10.1021/acs.jpcc.8b04013
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing Lead-Free All-Inorganic Tin Halide Perovskites by Ion Exchange

Abstract: Because of its thermal stability, lead-free composition, and nearly ideal optical and electronic properties, the orthorhombic CsSnI3 perovskite is considered promising as a light absorber for lead-free all-inorganic perovskite solar cells. However, the susceptibility of this three-dimensional perovskite toward oxidation in air has limited the development of solar cells based on this material. Here, we report the findings of a computational study which identifies promising RbyCs1–ySn(BrxI1–x)3 perovskites for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
59
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 78 publications
2
59
0
Order By: Relevance
“…An extensive monitoring of oxidation of CsSnI 3 in the air by using additives SnCl 2 , SnBr 2 , and SnI 2 has been carried out to measure electronic, optical absorption spectrum with time and reported that it exhibits the highest stability by inhibiting the crystallization/decomposition . The addition of SnF 2 lowers the background charge carrier density by neutralizing traps . The mesostructured CsSnI 3 displayed a SPCE of 2.02% with the addition of 20% SnF 2 as an additive.…”
Section: Lead‐free Perovskitesmentioning
confidence: 99%
See 2 more Smart Citations
“…An extensive monitoring of oxidation of CsSnI 3 in the air by using additives SnCl 2 , SnBr 2 , and SnI 2 has been carried out to measure electronic, optical absorption spectrum with time and reported that it exhibits the highest stability by inhibiting the crystallization/decomposition . The addition of SnF 2 lowers the background charge carrier density by neutralizing traps . The mesostructured CsSnI 3 displayed a SPCE of 2.02% with the addition of 20% SnF 2 as an additive.…”
Section: Lead‐free Perovskitesmentioning
confidence: 99%
“…[213] The thin films of CsSnIBr 3 were fabricated with the addition of hypophosphorous acid (HPA) with thermal stability up to 473 K achieving a SPCE of 3% that last for over 77 d. [193] The results of a computational study on mixed cesium perovskite Rb y Cs 1−y Sn (Br x I 3−x ) 3 as a light absorber have revealed that the substitution of Rb + for Cs + enhanced the quality of perovskite film and its practical applicability in perovskite solar cells. [214] Another study on CsSnI 3 and CsSnI 3−x Br x as light absorbers in n-i-p devices structure reported an efficiency of 2%. CsSnI 3 has a small bandgap of 1.27 eV to a near-infrared absorption onset to 950 nm and exhibited a high charge carrier density up to27.67 mA cm −2 .…”
Section: Tin-based Perovskitesmentioning
confidence: 99%
See 1 more Smart Citation
“…This substitution can not only result in long‐term stability in air but also maintain the high‐symmetry cubic structure with a different halogen X (X = Cl, Br, I). Furthermore, it is expected that the absorption range of A 2 SnX 6 can be simply altered by changing the halogen composition, which is beneficial to high‐performance solar cells and wavelength‐tuneable photodetectors …”
Section: Introductionmentioning
confidence: 99%
“…It is also worth mentioning that, although the reaction enthalpies of reaction 2 are slightly positive (Figure 4f), such reactions are typically driven by entropy of mixing. [36] The addition of GA + cations accelerates the conversion of δ-CsPbI 3 to the perovskite (Figure 3i). We estimate the mixing enthalpy (ΔH mix ) for the ternary mixing of Cs + , GA + , and FA + in the perovskite phase relative to the binary compounds by…”
mentioning
confidence: 99%